2021
DOI: 10.3389/fpls.2021.635732
|View full text |Cite
|
Sign up to set email alerts
|

AtSEC22 Regulates Cell Morphogenesis via Affecting Cytoskeleton Organization and Stabilities

Abstract: The plant cytoskeleton forms a stereoscopic network that regulates cell morphogenesis. The cytoskeleton also provides tracks for trafficking of vesicles to the target membrane. Fusion of vesicles with the target membrane is promoted by SNARE proteins, etc. The vesicle-SNARE, Sec22, regulates membrane trafficking between the ER and Golgi in yeast and mammals. Arabidopsis AtSEC22 might also regulate early secretion and is essential for gametophyte development. However, the role of AtSEC22 in plant development is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 95 publications
(126 reference statements)
0
12
0
Order By: Relevance
“…MAG2 also interacts with ER-localized Qa-SNARE AtSYP81 and Qb-SNARE AtSec20 to promote membrane fusion ( Li et al, 2013 ). In the mag2 , mip1 , mip2 , and mip3 mutants, ER export of SSP precursors is blocked, which results in accumulation of proteins inside the ER and serious ER stress ( Li et al, 2006 , 2013 ; Zhao et al, 2018 ; Guan et al, 2021 ). In order to explore the role of MAL in vesicle transport, we first performed yeast two hybrid analysis to detect the interaction between MAL and SNARE and MAG2 complex subunits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAG2 also interacts with ER-localized Qa-SNARE AtSYP81 and Qb-SNARE AtSec20 to promote membrane fusion ( Li et al, 2013 ). In the mag2 , mip1 , mip2 , and mip3 mutants, ER export of SSP precursors is blocked, which results in accumulation of proteins inside the ER and serious ER stress ( Li et al, 2006 , 2013 ; Zhao et al, 2018 ; Guan et al, 2021 ). In order to explore the role of MAL in vesicle transport, we first performed yeast two hybrid analysis to detect the interaction between MAL and SNARE and MAG2 complex subunits.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that MAL plays a minor role in protein transport and that it is functionally redundant with MAG2. Since abnormal accumulation of proteins in the ER lumen induces ER stress ( Li et al, 2006 , 2013 ; Zhao et al, 2018 ; Guan et al, 2021 ), we detected the expression of ER stress markers. Western blot of BiP1/2, a common ER stress marker, indicated that their protein accumulation was significantly increased in all the mutants, especially in the mal-1 mag2-1 double mutant ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, SYP73 anchors the ER to the actin cytoskeleton to maintain the integrity and fluidity of the ER ( Moreau et al, 2007 ; Cao et al, 2016 ). R-SNARE SEC22 is located in the ER, Golgi apparatus, and cytoplasm ( Guan et al, 2021 ). Sec22-4 shows shorter primary roots, dwarf plants, sterility, and abnormal epidermal cells.…”
Section: Snares Regulate Root Growth and Developmentmentioning
confidence: 99%
“…Sec22-4 shows shorter primary roots, dwarf plants, sterility, and abnormal epidermal cells. AtSEC22 plays an important role in membrane transport and cytoskeletal dynamics during plant development ( Chatre et al, 2005 ; El Kasmi et al, 2011 ; de Marcos Lousa et al, 2016 ; Guan et al, 2021 ). The vamp714 transfer DNA (T-DNA) insertional mutants grown in soil develop a shorter primary root and fewer lateral roots, have abnormal gravity responses, and disordered root cell arrangements.…”
Section: Snares Regulate Root Growth and Developmentmentioning
confidence: 99%
“…The function of Arabidopsis SEC22 and SED5 homologs SYP31 and SYP32 in Golgi structure maintenance has been demonstrated. In sec22 knock-out ( El-Kasmi et al, 2011 ) and knock-down ( Guan et al, 2021 ) mutants, Golgi stacks appear fragmented, with a number of vesicles surrounding the cisternal remnants. A recent study from our lab demonstrates that loss function of SYP31 and SYP32, the only two Qa-SNAREs localized at plant Golgi, impairs the trafficking between ER and Golgi where mCherry-HDEL is not located to the ER, rather it is rerouted to the vacuole ( Rui et al, 2021 ).…”
Section: Er-golgi Transportmentioning
confidence: 99%